Experimentals, bottoms, risk-reducers and clubbers: exploring diverse sexual practice in an Internet-active high-risk behaviour group of men who have sex with men in Sweden. Issue 6 (2nd June 2016) - Persson, Kristina Ingemarsdotter; Tikkanen, Ronny; Bergström, Jakob; Berglund, Torsten; Thorson, Anna; Forsberg, Birger C.
Abstract: This study aimed to identify sub-groups of men who have sex with men at high risk of HIV infection. Data from the Swedish MSM2013 survey were analysed with a focus on respondents ( n = 714) who reported having had unprotected anal intercourse with male casual partner(s) in the past 12 months. Weighted Latent Class Analysis with covariates and distal outcomes was conducted to identify sub-groups of men sharing the same sexual practice characteristics. Four latent classes emerged: experimentals, bottoms, risk-reducers and clubbers. Experimentals appeared to differ most from the other classes. They had extensive experience of barebacking, the use of poppers and fisting. Higher number of casual male sex partners and reporting having HIV were predictors for belonging to experimentals. No evidence for an association between self-rated HIV prevention knowledge and taking less part in risky practices was found. Hence, knowledge-intensive interventions may not be the best fit for reducing HIV transmission. This diversity of men based on similar sexual practice patterns should be taken into account when designing future HIV prevention interventions.